Primary Health Care Under One Roof (PHCUOR) in Nigeria inRetrospect: Successes and Challenges and the Possible WayForward (Western Journal of Medical and Biomedical Sciences, 2025)
Primary Health Care (PHC) was the grass-root management approach to achieving the goal of “Health for all by the year2000.” It is the first level care model of the National Health System where it is strategically positioned to be the firstpoint of contact for the health challenges of individuals and families in the communities. Over the years, Nigeria hasmade several attempts to implementing PHC, however the fragmentation the health system is experiencing in theprovision of health services and management of resources has caused a major setback. In an attempt to resolve thesechallenges facing the Nigerian health care system, the policy of bringing primary health care under one roof (PHCUOR)was adopted. This paper reviews the successes
Keywords: Health For All; Nigerian Health System; PHCUOR; Primary Health Care